2020
DOI: 10.1212/wnl.0000000000010250
|View full text |Cite
|
Sign up to set email alerts
|

Acute necrotizing encephalopathy with SARS-CoV-2 RNA confirmed in cerebrospinal fluid

Abstract: Here we report a case of Covid-19-related acute necrotizing encephalopathy (ANE) where SARS-CoV-2 RNA was found in cerebrospinal fluid (CSF) 19 days after symptom onset after testing negative twice. Even though monocytes and protein levels in CSF were only marginally increased, and our patient never experienced a hyperinflammatory state, her neurological function deteriorated into coma. Magnetic resonance imaging of the brain showed pathological signal symmetrically in central thalami, subinsular regions, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
294
3
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 226 publications
(305 citation statements)
references
References 8 publications
6
294
3
2
Order By: Relevance
“…While there was a small fraction of case reports and studies that showed its presence in CSF RT-PCR [ During our analysis, we found four cases where CSF IGM was positive [17,37],whereas Wang et al reported a case where both IgG and IgM antibodies against COVID -19 were positive [17]. In addition, CSF IGG was positive for COVID-19 in 2 cases [5,16].…”
Section: Discussionmentioning
confidence: 65%
“…While there was a small fraction of case reports and studies that showed its presence in CSF RT-PCR [ During our analysis, we found four cases where CSF IGM was positive [17,37],whereas Wang et al reported a case where both IgG and IgM antibodies against COVID -19 were positive [17]. In addition, CSF IGG was positive for COVID-19 in 2 cases [5,16].…”
Section: Discussionmentioning
confidence: 65%
“…However, the analyzed data further suggest that the prevalence of LA is higher in this patient population than expected for age. Other possible interpretations may include encephalitis as suggested in several reports (Anzalone et al, 2020;Asfar et al, 2020;Espinosa et al, 2020;Hayashi et al, 2020;Kremer et al, 2020), acute necrotizing encephalitis (Virhammar et al, 2020), encephalomyelitis (Abdi et al, 2020;Zoghi et al, 2020), demyelination (Zanin et al, 2020;Parsons et al, 2020;Zoghi et al, 2020), or microangiopathy (Fischer et al, 2020). Therefore, we encourage future studies to report more detailed description of the WM changes in order to establish differential characteristics of COVID-19-related vs. age-related changes in WM.…”
Section: Discussionmentioning
confidence: 72%
“…Diffuse subcortical and deep WM abnormalities were the most prominent. A cumulative of 62/124 (50%) of cases presented brain abnormality in either anterior areas [D (Asfar et al, 2020); N (Hepburn et al, 2020); α (Zanin et al, 2020), X : 9/242 cases, Z (Virhammar et al, 2020) (Zanin et al, 2020). Unspecified brain location for brain waves slowing on EEG recording was reported in four cases [G (Espinosa et al, 2020); H (Fischer et al, 2020); U (Parsons et al, 2020); Z (Virhammar et al, 2020).…”
Section: Topography Of Brain Abnormalities In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…53,64,66 Nevertheless, CSF from a small subset of patients with encephalitic features did test positive for SARS-CoV-2 RNA. 70,71 Seizures have been reported in SARS-CoV-2 patients; in a Chinese cohort, 4/78 hospitalized patients (0.5%) suffered at least one seizure. 40 This was mirrored in a Spanish cohort, where 6/841 hospitalized patients (0.7%) had at least one seizure.…”
Section: Neurological Complicationsmentioning
confidence: 99%